Determination of Competence, Motivation and Work Environment Towards Performance Achievement in the Intervening of Work Satisfaction of Community Health Center Employees in Kundur Island, Karimun Regency - Surawan SURAWAN; Chablullah WIBISONO; Sajiyo SAJIYO (PT Keberlanjutan Strategis Indonesia, 2024)
The UPT Puskesmas on Kundur Island has performance achievements in the poor category, but data has also been found showing that the performance achievements of existing employees are in the good category. Quantitative research aimed at determining the determination of Competence, Motivation, Work Environment on Performance Achievement in Intervening Employee Job Satisfaction. It was concluded that there was a significant determination of employee competence and job satisfaction on employee performance, there was no significant determination of work motivation and work environment on employee performance achievement, there was no significant determination of work competence and motivation on job satisfaction. Then there is a significant determination of the work environment on job satisfaction. It was also concluded that there was no significant determination of employee competence, work motivation and work environment on improving performance in employee job satisfaction interventions. It is recommended that elements of the UPT Puskesmas leadership on Kundur Island, Karimun Regency, discuss with the Puskesmas performance achievement evaluation team regarding performance achievement benchmarks based on employee competency factors. again regarding the suitability of the work environment in terms of its influence on performance achievement, and as soon as possible take solution action regarding the presence of employees who feel less motivated to improve or maintain their performance achievement.